A postgraduate Optimum Birth module to increase midwives' readiness to work in midwifery‐led settings: A mixed‐methods evaluation. Issue 3 (21st September 2018) - Coates, Rose; Rocca‐Ihenacho, Lucia; Olander, Ellinor; Ayers, Susan; Salmon, Debra
Abstract: Background: Midwifery‐led birth settings have been recommended as the most cost‐effective birthplaces for healthy women experiencing uncomplicated pregnancies. However, midwives complete most of their training in obstetric units where birth interventions are common. To prepare for working in a midwifery‐led setting training is a key priority. This study evaluated a postgraduate‐level midwifery module on Optimum Birth (defined as birth which supports physiology and empowerment, avoiding unnecessary intervention) designed to prepare midwives for supporting women in midwifery‐led settings. Methods: A mixed‐methods design was employed. Pre‐module and post‐module questionnaires measured attitudes, knowledge, confidence, and learning outcomes. Qualitative data collection included a final‐day focus group and 8‐ to 10‐week follow‐up interviews. The target for recruitment was 15 postgraduate midwives. Fifteen midwives practicing in three London boroughs enrolled of whom 14 completed the module. Pre‐total and post‐total scores were analyzed with paired‐sample t tests. Qualitative data were analyzed using thematic analysis. Results: Quantitative and qualitative data indicated that the module increased participants' self‐reported skills, knowledge, and confidence in practicing Optimum Birth. Qualitative data indicated ways in which midwives were implementing changes to promote Optimum Birth in their place of work. Attitudes were highly positive pre‐module and post‐module. Conclusions: The Optimum Birth module provided appropriate training for preparing midwives for the shift toward working in midwifery‐led settings. Midwifery leaders and managers should implement strategies to develop midwives' philosophy, knowledge, and skills to increase their readiness to work in midwifery‐led birth settings.